Development and Characterization of Pineapple Leaf Fibre Reinforced with Graphene and Fibre Glass Composites for Aerospace Application - Noor Ezzat Nafie Noor Azman; Mohd Fadhli Zulkafli; Safri, Syafiqah Nur Azrie (Progress in Aerospace and Aviation Technology, 2024)
Natural fibre-based composites such as Pineapple leaf fibre (PALF) are valued for their environmental friendliness and unique properties, can be combined with graphene and glass fibres to create advanced aerospace composites. This study investigates the effects of graphene content and PALF composition on the mechanical properties of the composite. PALF is made using environmentally friendly methods, with graphene treated for better integration and fibre glass added through layering. This study compares the strength and flexibility of two samples with different PALF-to-fibreglass ratios: 50:50 and 70:30, and one sample with a 70:30 PALF-to-fibreglass ratio reinforced with 1% graphene, using tensile and flexural tests. The 70:30 composition ratio results in a lower maximum tensile strength and Young’s modulus, but a higher bending stress than the 50:50 ratio due to the higher volume of PALF in the sample. 70:30 PALF/fibreglass reinforced with 1% graphene is stiffer, resulting in a higher Young’s modulus compared to the sample without graphene. There is a slight decrease in flexural strength for the 70:30 PALF/fibreglass ratio reinforced with 1% graphene, while still maintaining superior bending stress strength compared to 50:50 ratio compositions. From the SEM test, PALF/fibreglass samples exhibited fibre pull-out, while 70:30 samples reinforced with graphene showed fibre breakage. Graphene enhanced the bonding between fibres and resins, leading to the breakage. Without graphene, weaker bonding led to fibre pull-out. Therefore, the PALF/fibreglass reinforced with graphene has the potential for aerospace applications, particularly in components subjected to high bending stress, such as aircraft wings or the horizontal tail.